On local anesthetic action of some dimethylacetamide compounds - Andrei Novikov; Ekaterina Blinova; Elena Semeleva; Karina Karakhanjan; Mikhail Mironov; Dmirty Blinov; Yuliya Krainova; Dmitry Pakhomov; Olga Vasilkina; Elena Samishina (Belgorod National Research University, 2018)
The study aim was to explore local anesthetic properties of some tertiary and quaternary derivatives of dimethylacetamide. Materials and methods. The study was performed on white laboratory mice and rats of both sexes, male Agouti guinea pigs, and isolated sciatic nerves of lake frog. In the focus of the study there were two quaternary and eight tertiary compounds of dimethylacetamide with substituted anion with some amino and carbonic acids residue. A local anesthetic property was predicted by computational analysis. Acute toxicity of the most promising substances was studied in mice through subcutaneous route. Local anesthetic activity of tertiary compounds LKhT-3-00, LKhT-4-00 and quaternary LKhT-12-02 was studied on models of terminal, infiltration and conduction anesthesia. The influence of substances on mixed nerve conduction was investigated on lake frog's isolated sciatic nerves. Results and discussion. The greatest probability of the local anesthetic activity during computational analysis was estimated for the tertiary derivatives of dimethylacetamide LKhT-3-00 and LKhT-4-00 and for the quaternary compound LKhT-12-02. According to their toxicological profile, the compounds belong to moderately toxic substances (class 3). On the model of terminal and infiltration anesthesia, substances LKhT-3-00 and LKhT-4-00 at concentrations of 0.5-1% rapidly cause deep and prolonged anesthesia. On the models of conduction anesthesia, the quaternary derivative of dimethylacetamide LKhT-12-02 has the greatest analgesic effect. The duration of the effect of the substance is over 3 hours. All the investigated compounds block sciatic nerve conduction. The longest effect is registered for LKhT-12-02. Conclusions. Dimethylacetamide derivatives at concentrations of 0.5-1.0% exhibit a local anesthetic activity, and are effective for terminal, conduction and infiltration anesthesia. Their effect is due to blockade of nerve conduction.